2018
DOI: 10.1128/jb.00294-18
|View full text |Cite
|
Sign up to set email alerts
|

MsaB and CodY Interact To Regulate Staphylococcus aureus Capsule in a Nutrient-Dependent Manner

Abstract: has a complex regulatory network for controlling the production of capsule polysaccharide. In , capsule production is controlled by several regulators in response to various environmental stimuli. Previously, we described MsaB as a new regulator that specifically binds to the promoter in a growth phase- or nutrient-dependent manner. In addition to MsaB, several other regulators have also been shown to bind the same region. In this study, we examined the interactions between MsaB and other nutrient-sensing regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…The chromatin immunoprecipitation assays were performed as previously described (Sengupta, Jain, Wilkinson, & Jayaswal, ), with modifications as previously described (Batte et al, ). Fold change was calculated by the following equation: ( rsaD IP copy #/gyrA IP copy #)/( rsaD input copy #/ gyrA input copy number).…”
Section: Methodsmentioning
confidence: 99%
“…The chromatin immunoprecipitation assays were performed as previously described (Sengupta, Jain, Wilkinson, & Jayaswal, ), with modifications as previously described (Batte et al, ). Fold change was calculated by the following equation: ( rsaD IP copy #/gyrA IP copy #)/( rsaD input copy #/ gyrA input copy number).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this study, several other studies also reported increased levels of MsaB (also known as CspA) and oxidative stress-response proteins, including thioredoxin (Trx), in staphylococcal infections (29)(30)(31), highlighting their importance in stress response and their role in causing persistent S. aureus infections in the host. In our previous studies, we reported a regulatory role for the msaABCR operon (MsaB) in capsule production (32,33), biofilm development (34), antibiotic resistance (35), and the formation of persister cells in S. aureus (36). On transcriptomic analysis, deletion of the msaABCR operon in the USA300 LAC strain induced differential expression of more than 10 genes that are involved in resisting oxidative stress (36).…”
mentioning
confidence: 99%
“…Nevertheless, Rot as well as the DNA binding proteins CodY and SaeR are likely candidates for direct interference with the P cap promoter element. CodY represses many metabolic and virulence genes, including the cap operon (Pohl et al, 2009;Majerczyk et al, 2010), and binding of CodY to the P cap region has been demonstrated (Majerczyk et al, 2010;Batte et al, 2018;Lei and Lee, 2018). The two-component system (TCS) SaeRS regulates a number of virulence factors, with cap being one of the few genes repressed (Steinhuber et al, 2003;Luong et al, 2011;George et al, 2015).…”
Section: Introductionmentioning
confidence: 99%